The influence of word of mouth, attractiveness and brand image on customer satisfaction PT. Leffindo Jaya logistics in Batam city - Wiliayanto, Wiliayanto; Sunarto Wage (SEAN Institute, 2024)
This research was conducted to determine the influence of word of mouth, attractiveness and brand image on customer satisfaction at PT Leffindo Jaya Logistic in Batam City where each variable has problems such as the services provided are still not trusted and are not popular with customers. There are some people that are more trusting to Word of Mouth than official ads or promotion, there are some WoM that PT Leffindo Jaya Logistics do not show responsibilities and thus causing customer satisfaction of PT Leffindo Jaya Logistics to go down. Also the recommendation of families, friends, and business partners were considered more objectively and seriously by potential customers. So this type of research is quantitative research to test the relationship between hypothesized variables. This research has a population with a total of 100 customers (58 men and 42 women) who were given questionnaires. This research was conducted at Sagulung District, Tembesi Village, Batam City. This research uses a purposive sampling method. The results of this research show that the variables word of mouth, attractiveness and brand image are significantly positive on customer satisfaction. With this research conducted, researcher hope this will help that small-middle sized logistics services company to know what is lacking from their services so they can improve their service from local to international, and pay more attention to every little details to keeps improving customer satisfaction especially PT Leffindo Jaya Logistics, as a few dissatisfaction could make their potential customers to turn away and seeks alternatives choice.